The Influence Of Financial Technology Products, Investment Knowledge, Student Investment Interest And Return On Investment Decisions. Case Study On Students In Sidoarjo Regency, East Java - Ulil Fadilah; Solihin Solihin; Karsam Karsam (Eduvest - Journal of Universal Studies, 2024)
Investment decisions in personal financial management especially for students is crucial because investment is a process of learning to manage finances, starting now and in the future. Low knowledge about planning an often makes students experience fraud, because offers from investment returns are also very tempting. Based on the phenomenon, this study aims to determine the effect of financial technology, investment literacy, investment interest, and return investment tolerance on investment decisions. This research was conducted by distributing questionnaires to respondents with the criteria of students at the University of Sidoarjo city in study program, economy & business class. The number of research respondents was 288 students and data management used SmartPLS 3.2.8 analysis techniques. The results of this study state that financial technology, investment literacy, investment interest has a positive and significant effect on investment decisions, while return investment have a insignificant effect on investment decisions of University student University of Sidoarjo city in study program economy & business.